Oxidizable carbon and humic substances in rotation systems with brachiaria/livestock and pearl millet/no livestock in the Brazilian Cerrado - Loss, A.; Pereira, M. G.; Perin, A.; Beutler, S. J.; Anjos, L. H. C. dos (Spanish Journal of Agricultural Research, 2013)
The crop-livestock integration system significantly increases the carbon content in chemical fractions of soil organic matter (SOM). This study aimed to evaluate chemical indicators of SOM attributes for sites under brachiaria/livestock and pearl millet/no livestock in Goias, Brazil. A third area covered with natural Cerrado vegetation (Cerradão) served as reference. Soil was randomly sampled at 0-5, 5-10, 10-20 and 20-40 cm. Total organic carbon stocks (TOC), oxidizable carbon fractions (OCF) (F1>F2>F3>F4), carbon content in the humin (C-HUM), humic acid (C-HAF) and fulvic acid (C-FAF) fractions were evaluated. F1/F4, F1+F2/F3+F4, C-HAF/C-FAF and (C-HAF+C-FAF)/C-HUM indices were calculated, as well as stocks chemical SOM fractions. Brachiaria/livestock produced greater TOC stocks than pearl millet/no livestock (0-5, 5-10 and 10-20 cm). In terms of OCF, brachiaria/livestock generally exhibited higher levels in F1, F2, F4 and F1/F4 than pearl millet/no livestock. C-HUM (0-10 cm) and C-HAF (0-20 cm) stocks were larger in brachiaria/livestock than pearl millet/no livestock. Compared to the Cerradão, brachiaria/livestock locations displayed higher values for TOC (5-10 and 10-20 cm), C-HAF and C-HAF/C-FAF (5-10 cm) stocks. TOC, C-HAF stock and OCF show that land management with brachiaria/livestock was more efficient in increasing SOM than pearl millet/no livestock. Moreover, when compared with pearl millet/no livestock, brachiaria/livestock provided a more balanced distribution of very labile (F1) and recalcitrant (F4) carbon throughout soil layers, greater SOM humification. Brachiaria/livestock leads to higher values of F1 and F4 in depth when compared to pearl millet/livestock and provides a more homogeneous distribution of C-FAF and C-HAF in depth compared to Cerradão.